NDUFA4L2 Regulated by HIF-1α Promotes Metastasis and Epithelial–Mesenchymal Transition of Osteosarcoma Cells Through Inhibiting ROS Production - Xu, Wen-Ning; Yang, Run-Ze; Zheng, Huo-Liang; Jiang, Lei-Sheng; Jiang, Sheng-Dan (Frontiers in Cell and Developmental Biology, 2020)
Osteosarcoma (OS) accounts for a large proportion of the types of bone tumors that are newly diagnosed, and is a relatively common affliction. However, there are still no effective treatments for this affliction. One interesting avenue is research is related to the mitochondrial NDUFA4L2 protein, which is encoded by the nuclear gene and is known to be a critical mediator in the regulation of cell survival. Thus, in this study, we aimed to investigate the effect of NDUFA4L2 upon the metastasis and epithelial–mesenchymal transition of OS. We found that NDUFA4L2 protein expression was up regulated in hypoxic conditions. We also used 2-ME and DMOG, which are HIF-1α inhibitors and agonists respectively, to assess the effects related to decreasing or increasing HIF-1α expression. 2-ME caused a significant decrease of NDUFA4L2 expression and DMOG had the opposite effect. It was obvious that down-regulation of NDUFA4L2 had a direct interaction with measures of apoptosis of OS cells. Western blotting, wound healing analyses, Transwell invasion assays, and colony formation assays all indicated and supported that conclusion that NDUFA4L2 promoted OS cell migration, invasion, proliferation, and the epithelial–mesenchymal transition. During experiments, we incidentally discovered that autophagy and the introduction of an ROS inhibitor could be used to facilitate the rescuing of tumor cells whose NDUFA4L2 was knocked down. Our findings will help to further elucidate the dynamics underlying survival of OS cells and have provided a novel therapeutic target for the treatment of OS.